Comparison Of The Function Of Neutrophil Cells Oxidative Burst Among Various Group Ages - Dwi Setyawan; Gatot Sugiarto; Novira Widajanti (Current Internal Medicine Research and Practice Surabaya Journal, 2020)
Background: In old ages there is a change in the immune system along with the aging process called the term immunosenescence. Neutrophil cells play an important role in natural immunity because they are the first immune cells to be deployed in the body's defenses.Objective: To prove that there is a difference in the function of neutrophil cell oxidative burst in older age group compared with the younger age group as well as the tendency of decreased oxidative burst function of neutrophil cells with increasing age.Method: This is a cross-sectional observational analytic study involving 48 healthy subjects. The subjects were divided into 3 age groups: young age (18-40 years old), middle age (41-59 years old), and old age ≥60 years old). Each of them were examined for the function of neutrophil cells oxidative burst. The data were then analyzed using one-way ANOVA test. The result was considered significant if p<0.05.Results: The obtained mean age 59.26±8.03 years old. The mean age for young age group was 28.75±6.66 years old. The mean of middle age group was 50.19±5.46 years old. The mean age of old group was 66.38±3.83 years old. The mean of netrofil oxidative burst cell function was 96.83±2.7% with mean of young age being 98.57±0.98%, middle age 97.71±1.64%, and old age 94.20±3.56%. One way ANOVA comparison analysis showed a significant difference with p = 0.000 (significant when p <0.05). The result of Rank Spearman test showed significant result with r=-0.590 (p=0.000).Conclusion: There are differences in the function of neutrophil cells oxidative burst between young and old age groups. There is a negative trend between the age group and the function of neutrophil cell oxidative burst. The increase of age causes decrease in the function of neutrophil cells oxidative burst.